Clinical Significance of Tumor Surface Desmoplastic Reaction as a Predictor of Lymph Node Metastasis in Colorectal Cancer with Submucosal Invasion - Matsuda, Mitsuhiro; Sasaki, Morio; Sakamoto, Kazuhiro; Tomiki, Yuichi; Kamano, Toshiki; Kawai, Ken; Kasamaki, Shinji; Watanabe, Tomoo (Nippon Shokaki Geka Gakkai zasshi, 2005)
Purpose: We studied the usefulness of tumor desmoplastic reaction (DR) as a predictor of lymph node metas-tasis in colorectal cancers with submucosal invasion. Methods: Subjects were 59 patients who underwentsurgical resection of colorectal cancer with submucosal invasion, 9 cases (15.3%) of whom were positive forlymph node metastasis (n). Clinicopathological factors and DR expression, especially DR expression on the tu-mor surface and DR expression in preoperative biopsy specimens were also studieded. DR was identified byimmunohistochemistry, and a result of α-SMA (+) and desmin (-) was defined as DR-positive. Results: DR expression was observed in 50 of 59 cases (84.7%) of colorectal cancers with submucosal invasion, while DR expression on the tumor surface was found in 24 cases (41.4%). In the depth of cancer invasion, DR ex-pression was observed in 8 of 14 (57.1%) sm1 cases compared to 42 of 43 (93.3%) sm2, 3 cases, with a signifi-cantly higher rate in sm2, 3 cases. DR expression on the tumor surface was seen in 16 of 50 (32%) n (-) casescompared to 8 of 9 (88.9%) n (+) cases, with a significantly higher rate in n (+) cases. Among 24 tumorsurface DR-positive cases, preoperative biopsies were conducted in 21, yielding 45 samples. Some 22 of the 45biopsy samples (48.8%) were also found to express DR. Among 9 n (+) cases, 7 underwent preoperative bi-opsies and 6 (85.71%) were DR-positive in biopsy samples. Conclusion: Our results indicated the usefulnessof tumor surface DR expression as a predictor of lymph node metastasis in colorectal cancers with submu-cosal invasion, and suggests the possibility of predicting lymph node metastasis from DR expression in preop-erative biopsy specimens.